Triple Synchronous Primary Neoplasms of the Cervix, Endometrium, and Ovary: A Rare Case Report and Summary of All the English PubMed-Indexed Literature - Ahmed Abu-Zaid; Mohannad Alsabban; Mohammed Abuzaid; Osama Alomar; Hany Salem; Ismail A. Al-Badawi (Hindawi Limited, 2017)
The incidence rate of triple or more synchronous primary neoplasms of the female genital system is exceedingly uncommon. To the best of our knowledge, only 13 such cases have been reported in the PubMed-indexed English literature. Herein, we report a single case of triple synchronous primary neoplasms of the cervix, endometrium, and left ovary with three distinct histological patterns that were not reported previously. Moreover, we briefly present a summary table of all the English PubMed-indexed cases of triple or more synchronous primary neoplasms of the female genital system (n=13).